Advances in Engineered Cementitious Composites : A Comprehensive Review - Norsuzailina, Mohamed Sutan; Faisal Amsyar, Redzuan; Abdul Razak, Abdul Karim; Norazzlina, M. Sa'don (American Concrete Institute, 2025)
Engineered cementitious composites (ECC) represent a significant innovation in construction materials due to their exceptional flexibility, tensile strength, and durability, surpassing traditional concrete. This review systematically examines the composition, mechanical behavior, and real-world applications of ECC, with a focus on how fiber reinforcement, mineral additives, and micromechanical design improve its structural performances. The present study reports on the effects of various factors, including different types of mineral admixtures, aggregate sizes, fiber hybridization, and specimen dimensions. Key topics include ECC’s strain hardening properties, its sustainability, and its capacity to resist crack development, making it ideal for high-performance infrastructure projects. Additionally, the review discusses recent advancements in ECC technology such as hybrid fiber reinforcement and the material’s growing use in seismic structures. The paper also addresses the primary obstacles, including high initial costs and the absence of standardized specifications, while proposing future research paths aimed at optimizing ECC’s efficiency and economic viability.